Determinants Of Malnutrition Based On The Composite Index Of Anthropometric Failure (CIAF) - Eka Safitri Yanti; Tesza Rezky Permata; Rohmatun Karimah (Poltekkes Kemenkes Surakarta, 2022)
Background: Malnutrition in toddlers (under five years) is known to cause disturbances in growth and development. The Composite Index of Anthropometric Failure (CIAF) is an alternative anthropometric that specifying and combining various growth failures that occur. Methods: A descriptive quantitative study with a cross-sectional approach was carried out for 10 (ten) months in 2022. A total of 155 samples of toddlers (aged 6 months to 5 years) were taken using the multistage random sampling technique. The instruments used include questionnaires about the characteristics of parents, family economy, family awareness about nutrition, and health seeking behavior. The tools to detect malnutrition are a calibrated digital stature meter and weight scales. The data was analyzed through Chi Square, and Mann-Whitney is used as an alternative if the data found does not meet the requirements. Results: Of the 155 children under five examined, 48.4% or almost half of the respondents experienced growth failure. Most growth failure was in the stunting and underweight category (21.3%) and the least was in the wasting only category (1.3%). Family awareness about nutrition and health seeking behavior were not found to be related to the nutritional status of children, where statistically the prevalues obtained were 0.217 and 0.173, respectively. Conclusion: Based on the CIAF, none of the factors studied were found to have an association with malnutrition. Further research is needed by examining a wider scope of variables and providing more intensive training to survey officers to obtain more accurate data.